Study on the embrittlement of flash annealed Fe85.2B9.5P4Cu0.8Si0.5 metallic glass ribbons. (15th October 2018) - Minnert, Christian; Kuhnt, Markus; Bruns, Sebastian; Marshal, Amalraj; Pradeep, Konda Gokuldoss; Marsilius, Mie; Bruder, Enrico; Durst, Karsten
Abstract: Nanocrystalline Fe-based alloys have excellent soft magnetic properties, but their application is limited due to annealing induced embrittlement. In this work the embrittlement of flash annealed Fe85.2 Si0.5 B9.5 P4 Cu0.8 (at.%) ribbons was investigated using two-point bending and tensile tests as well as nanoindentation testing. In addition, fracture surfaces of notched tensile specimens were analyzed in dependence on annealing temperature and correlated to mechanical and structural transitions. The amorphous ribbons have been flash annealed for 10 s at temperatures between 330 °C and 540 °C under an applied tensile stress of 20 MPa. X-ray diffraction and atom probe tomography were used to analyze the phase formation, microstructure and elemental partitioning. The results of two-point bending tests show a sharp transition from ductile to brittle behavior at annealing temperatures between 330 °C and 350 °C. The stress intensity factor is decreasing from 70.4 MPa m to 3.2 MPa m . Thus, embrittlement takes place before the onset of crystallization at 400 °C. This embrittlement is related to a reduced shear band activity as a more localized shear activity during two-point bending. Nanoindentation results suggest a slight increase in the shear transformation zone volume, which could be related to a relaxation of free volume. Graphical abstract: Highlights: Mechanical testing of (annealed) Fe-based metallic glass ribbons in terms of stress intensity factor and bending ductility. APT analysis shows the formation of Cu clusters upon annealing above the crystallization temperature. Embrittlement caused by a reduced shear band activity, a reduced free volume content and increasing STZ volume.